2013
DOI: 10.6061/clinics/2013(10)10
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic effects of crocetin in scleroderma fibroblasts and in bleomycin-induced sclerotic mice

Abstract: OBJECTIVE:To investigate the antifibrotic effects of crocetin in scleroderma fibroblasts and in sclerotic mice.METHODS:Skin fibroblasts that were isolated from three systemic scleroderma (SSc) patients and three healthy subjects were treated with crocetin (0.1, 1 or 10 μM). Cell proliferation was measured with an MTT assay. Alpha-smooth muscle actin was detected via an immunohistochemical method. Alpha 1 (I) procollagen (COL1A1), alpha 1 (III) procollagen (COL3A1), matrix metalloproteinase (MMP)-1 and tissue i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This conversion has been recapitulated with TGFβ treatment of in vitro cultures of fibroblasts (2, 242526). Myofibroblasts usually undergo deactivation and apoptosis, dedifferentiation, or senescence in the latter stages of the wound healing process, the time when matrix reabsorption and TGFβ signaling terminate and redox homeostasis is restored (5, 7, 21, 23, 24, 2728293031). The danger in fibroblast plasticity arises when the precipitating injury leads to excessive fibrogenic milieu activation wherein myofibroblast differentiation or persistence occurs, leading to wound strengthening through disproportionate collagen deposition, fiber alignment, and excessive force contraction, in part because myofibroblasts contribute to wound repair, not tissue regeneration (3, 7, 28).…”
Section: Pathology In Tissue Fibrosis: Differentiation Into the Myofimentioning
confidence: 99%
See 1 more Smart Citation
“…This conversion has been recapitulated with TGFβ treatment of in vitro cultures of fibroblasts (2, 242526). Myofibroblasts usually undergo deactivation and apoptosis, dedifferentiation, or senescence in the latter stages of the wound healing process, the time when matrix reabsorption and TGFβ signaling terminate and redox homeostasis is restored (5, 7, 21, 23, 24, 2728293031). The danger in fibroblast plasticity arises when the precipitating injury leads to excessive fibrogenic milieu activation wherein myofibroblast differentiation or persistence occurs, leading to wound strengthening through disproportionate collagen deposition, fiber alignment, and excessive force contraction, in part because myofibroblasts contribute to wound repair, not tissue regeneration (3, 7, 28).…”
Section: Pathology In Tissue Fibrosis: Differentiation Into the Myofimentioning
confidence: 99%
“…Receptor modulation: wide study of the endothelin receptors has led to a myriad of clinical trials based upon basic research conducted with fibroblasts. Levels of the vasoactive peptide ET-1 and procontractile proteins are significantly increased in SSc fibroblasts, which enhance their ability to contract collagen matrix compared to normal fibroblasts (26, 31, 32). Treatment of normal and SSc human dermal fibroblasts with ET-1 promoted significant ECM production and matrix contraction through the endothelin A (ETA) receptor (32, 80).…”
Section: Direct Translation Of Fibroblast Research To Clinical Trialsmentioning
confidence: 99%
“…A recent study has discovered that crocetin treatment may protect against burn-induced small intestinal injury by inhibiting oxidative stress and inflammatory response ( 22 ). Furthermore, crocetin may alleviate cardiac, skin and lung fibrosis due to suppression of reactive oxygen species-dependent signaling pathways or a reduction in endothelin-1 ( 23 , 24 ). It has also been reported that geniposide is able to suppress the release of pro-inflammatory cytokines tumor necrosis factor-α, interleukin-6 and interleukin-1β in vitro and in vivo , and is also able to block the phosphorylation of nuclear factor-κB, p65 and p38, as well as inhibiting the expression of extracellular signal-related kinases (ERKs) and c-Jun N-terminal kinases in lipopolysaccharide-stimulated primary mouse macrophages ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Crocetin is an apocarotenoid dicarboxylic acid extracted from Crocus flowers and Gardenia jasminoides fruits. Crocetin inhibited the proliferation of normal and SSc fibroblasts and the trans-differentiation of SSc fibroblasts into myofibroblasts; in the bleomicin mouse model of SSc repeated intraperitoneal injection of crocetin alleviated J U S T A C C E P T E D skin and lung fibrosis in association with decreased levels of mRNAs for type 1 collagen and endothelin-1 in skin and lung [171].…”
Section: Crocetinmentioning
confidence: 98%